PERENCANAAN PEMBANGUNAN SEKTOR PERTANIAN DI DESA BILA KABUPATEN SIDENRENG RAPPANG - Rifni Nikmat Syarifuddin; Muh. Irwan; Saifullah Saifullah (Jurnal Bisnis dan Kewirausahaan, 2019)
Production of rice plants in Sidrap Regency from 2014 to 2017 has increased every year, so this allows the potential of Sidrap Regency in the agricultural sector to be very high. In this regard, the results of development in the agricultural sector can be measured by the value of the PDRB (Produk Domestik Regional Bruto) donated. but the increase in production every year apparently did not contribute to the PDRB significantly and even decreased, especially in Desa Bila. The research method used was quantitative descriptive and the population in this study were farmer groups in the Dua Pitue, Sidenreng Rappang, amounted to 105 people from 15 groups and the samples used were 53 people with random sampling techniques. Based on the results of the study it can be seen that the highest to lowest percentage of development planning indicators are consistency and realistic (83.25%), behavior and relationship of economic variables (81.00%), continuous supervision (78.75%), physical aspects (76.41%), and development goals (70.25%), this shows that agricultural development planning is categorized as good, but not maximized because the supervisory model used is indirect supervision, besides that in planning it is very much needed advice from the peope who are the target of developmen.